pH‐Sensitive Polymer Gels for EOR in Fractured Tight Reservoirs: Mechanistic and Performance Analysis - Liu, Siqi; Jia, Hu; Cao, Zuowei; Fu, Gaoqiang; Liu, Chao; He, Dongxu; Deng, Xuan; Yu, Zhigang (Journal of applied polymer science, 2025)
ABSTRACT Fractured tight reservoirs are characterized by dual‐permeability systems (matrix and fractures), where injected fluids predominantly channel through high‐conductivity fractures, resulting in inefficient energy replenishment. To mitigate this challenge, we engineered a pH‐responsive polymer gel system with balanced injectability and plugging strength. The gel comprises citric acid (0.1%–0.4%), nano‐silica (0.1%–0.4%), partially hydrolyzed polyacrylamide (HPAM; 0.3%–0.6%), and water‐soluble phenol‐formaldehyde (WSPF; 0.4%–1.0%). Experimental results demonstrated that the initial viscosity of the gel solution was controlled below 100 mPa·s (minimum: about 20 mPa·s), with gelation time adjustable between 20 and 40 h at 70°C. After aging for 7 days at 70°C, the storage modulus (15.0–30.0 Pa) significantly exceeded the loss modulus (1.0–3.0 Pa), indicating high elasticity and low viscosity. Long‐term stability tests in 70,000 MPa·m−1 saline formation water (70°C, 180 days) revealed retained storage modulus (> 15.0 Pa) and dehydration rate (< 10%). Breakthrough pressure gradients for the optimized formulation in 0.5–3.0 mm diameter slim pipes were 2.45–0.84 MPa·m−1, confirming robust fracture‐plugging capability. This study systematically evaluates the design, performance, and application potential of pH‐sensitive gels for enhancing oil recovery in fractured tight reservoirs. This study introduces a pH‐sensitive polymer gel for enhanced oil recovery in fractured tight reservoirs. Composed of citric acid, nano‐silica, HPAM, and phenol‐formaldehyde, the gel exhibits ultra‐low initial viscosity (≤ 100 mPa·s), tunable gelation (20–40 h), and robust stability (storage modulus > 15 Pa after 180 days). Its high breakthrough pressure gradient (0.84–2.45 MPa·m−1) ensures effective fracture plugging, improving sweep efficiency.